دور استقلاليّة المصارف المركزيّة في الحدّ من التّضخّم - عباس غادة; حبيب علاء (Latakia University Journal - Economic and Legal Sciences Series, 2014)
فيْ أيّامنا هذه، يعْتقد على نطاقٍ واسعٍ أنّ الدرجة المرتفعة لاستقْلاليّة المصْرف المركزيّ، والمصْحوبة بتفْويضٍ صريحٍ له منْ أجْل تقْييد التّضخّم، تعدّ أداةً مؤسّساتيّةً هامةً لضمان اسْتقْرار الأسْعار. تقدّم هذه الورقة اختباراً لمقْياس اسْتقْلاليّة المصْرف المركزيّ (GMT) المبْتكر منْ قبل (Grilli-Masciandaro-Tabellini) والمسْتند إلى تشْريْعات المصارف المركزيّة فيْ نهاية العام (2003)، حيث تمّ جمْع مؤشّرات الاسْتقْلاليّة لـ (82) مصْرفٍ مرْكزيٍّ فيْ نهاية العام (2003)، وقدْ أكّد التحْليْل أنّ معدّلات الاسْتقْلاليّة المرْتفعة ساْعدتْ فيْ المحافظة علىْ معدّلاتٍ منْخفظةٍ من التّضخّم. Nowadays, it is widely believed that a high degree of Central Bank Independence (CBI) coupled with some explicit mandate for the Central Bank (CB) to restrain inflation is an important institutional device to enusre price stability. This paper aims to examine the Grilli-Masciandaro-Tabellini (GMT) index of central bank (CB) independence, based on CB legislation as of end-2003. The researcher calculates indexes of central bank independence (CBI) for 82 central banks as of end-2003. Our analysis confirms that greater CBI has on average helped to maintain low inflation levels.